Cathodoluminescence and Photoluminescence of YPO4:Pr3+, Y2SiO5:Pr3+, YBO3:Pr3+, and YPO4:Bi3+. (27th January 2017) - Broxtermann, M.; den Engelsen, D.; Fern, G. R.; Harris, P.; Ireland, T. G.; Jüstel, T.; Silver, J.
Abstract : Herein we describe the synthesis, characterization, and cathodoluminescence of the UV emitting phosphors YPO4 :Pr 3+, Y2 SiO5 :Pr 3+, YBO3 :Pr 3+, and YPO4 :Bi 3+ . These photoluminescent UV phosphors exhibited strong luminescence in the UV part of the electromagnetic spectrum when excited by electron bombardment. Spectra have been recorded between 210 and 650 nm at electron beam energies of 5, 10 and 15 keV. The energy efficiencies of YPO4 :Pr 3+, Y2 SiO5 :Pr 3+, YBO3 :Pr 3+ and YPO4 :Bi 3+ in the UV range were 9.2%, 2.7%, 5.1%, and 7.2%, respectively at 15 keV. UV photoluminescence measurements were conducted using 160 nm excitation generated by combining a VUV monochromator with a deuterium lamp.